The Prevalence of Adverse Skin Reactions Associated with Face Mask Wearing among Students in Malaysia - Nur Aqilah Binti Mohd Nasir; Anish A/L Sarkurunatan; Muhammad Zulhelmi Bin Zulkifli Muhammaddun; Lim Xin Yu; Norhafizah Ab Manan (Asian Journal of Medicine & Health Sciences, 2023)
Background: Outdoor mask wearing has been mandatory for all Malaysians since its implementation by the Malaysian government due to Covid-19 outbreak. Although wearing a face mask has been shown to reduce the risk of virus transmission, this practice has also been associated with a variety of facial skin problems. Methods: This study aims to determine the prevalence of adverse skin reactions associated with the practise of wearing face masks. A cross-sectional study was conducted among undergraduate students at University of Cyberjaya from September 2021 to December 2021. Data were collected through a self-administered online questionnaire which assesses students’ perceptions on (i) attitude towards face mask utilisation, (ii) proper practice of face mask use, (iii) adverse skin reactions, and (iv) factors influencing face mask use. Results: Most respondents were female (76%) and aged between 18 to 22 years old (70%). Most participants wore face masks for less than 4h per day (61%) and 50% of the participants wore surgical face masks. 66.3% participants complained of adverse skin reactions. Acne was the most common (75%), followed by oily skin (62%) and facial itching (55%). The incidence of adverse skin reactions was found higher among females (69.8%), wearing face masks for longer durations (71.1%) and wearing surgical face masks (67.3%). Conclusion: Majority of the participants demonstrated good practice face mask utilisation. This study provides an opportunity to raise public awareness about facial mask hygiene so that interventions can be implemented to reduce the occurrence of adverse skin reactions.